2017
DOI: 10.1108/aaaj-07-2015-2139
|View full text |Cite
|
Sign up to set email alerts
|

Big Data and corporate reporting: impacts and paradoxes

Abstract: Purpose The purpose of this paper is to investigate the phenomenon of Big Data and corporate reporting, and to determine the impact of Big Data and the current Big Data state of mind with regard to corporate reporting, what accountant and non-accountant participants’ perceptions are of the phenomenon, what the accountants’ role is and will be in this regard, and what opportunities and risks are associated with Big Data and corporate reporting. Furthermore, this study seeks to identify the inherent technologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
119
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(127 citation statements)
references
References 32 publications
(100 reference statements)
3
119
0
5
Order By: Relevance
“…Our examination of the process of IFRS Taxonomy standardisation and its effects is timely in the context of 'big data' impacts on corporate reporting (Al-Htaybat & Alberti-Alhtaybat, 2017), and in particular given recent decisions of regulators in the EU and US concerning the use of IFRS Taxonomy. In December 2016, the European Securities and Markets Authority (ESMA) announced that EU-listed firms will be required to tag corporate IFRS reports using the IFRS Taxonomy from January 2020 (ESMA, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Our examination of the process of IFRS Taxonomy standardisation and its effects is timely in the context of 'big data' impacts on corporate reporting (Al-Htaybat & Alberti-Alhtaybat, 2017), and in particular given recent decisions of regulators in the EU and US concerning the use of IFRS Taxonomy. In December 2016, the European Securities and Markets Authority (ESMA) announced that EU-listed firms will be required to tag corporate IFRS reports using the IFRS Taxonomy from January 2020 (ESMA, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The ESRM leader used a wide range of skill sets to be to be successful. According to the author [1], these skills are less related to security knowledge Leading the enterprise's security risk management effort is about being supportive to the business objectives and the board's goals, and aligning the company with those and pushing the program as part of the board's overall business aims and objectives innovative business, we do not have to be a Chief Financial Officer (CFO) or developer or retailer; what we have to be is a very good generalist and a good leader, somebody who can make decisions and get people on highly innovative on different functions in the organizations to engaged in trust [5]. What we are able to provide is the change in management innovation and the use of an appropriate approach to solve problems.…”
Section: The Necessary Skill Smentioning
confidence: 99%
“…According to the , these skills are less related to security knowledge than they are in the business world. Leading the enterprise's security risk management effort is about being supportive to the business objectives and the board's goals, and aligning the company with those and pushing the program erall business aims and objectives [1]. To understand the pure and innovative business, we do not have to be a Chief Financial Officer (CFO) or developer or retailer; what we have to be is a very good generalist and a good leader, somebody who can make sions and get people on highly innovative on different functions in the organizations to .…”
Section: Setsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike modern ERP systems that contain mostly structured data with clear connections, Big Data offers the advantage of analyzing unstructured or semi-structured data from the entire economic environment, which has the potential of changing our perception of certain economic trends. Regarding the perception of accountants in practically use Big Data as a tool to create more accurate forecasts and to appropriately address particular problems, research has shown that the overall feedback is positive (Al-Htaybat & Alberti-Alhtaybat, 2017).…”
Section: Literature Review -Information Technologies and New Challengmentioning
confidence: 99%